UTILIZATION OF PALM KERNEL SHELL WASTE INTO A BRICKET - Sri Mulyati; Kevin Alvindo; Jubaidi Jubaidi (Poltekkes Kemenkes Bengkulu, 2023)
Oil palm shell is one of the palm oil processing wastes, which is quite large, reaching 60% of the production of kernel oil. The plantation waste can be processed into an artificial solid fuel which is more widely used as an alternative fuel called bio-briquettes. The researchers aim to utilize palm kernel shell waste (Palm Kernel Shell) into briquettes.This type of research is Quasi Experiment Design with the